Desarrollo de un sistema de tratamiento de aguas residuales industriales para la planta de producción de Asequimicos SAS (2018)
In the present work of degree developed a system of treatment of industrial residual waters for the plant of production of Asequimicos SAS. For the selection of the alternative treatment of wastewater generated by the washing processes of cans, areas, personal protection elements and equipment (mixer), a current diagnosis of the wastewater was developed, including the water balance of the plant, with the purpose of evaluating each of the effluents by means of a characterization made by an external laboratory (Environmental Laboratory of the Regional Autonomous Corporation) which allowed defining the critical parameters to be taken into account for the choice of the treatment alternative. After the diagnosis, several treatment alternatives were proposed and the viability of each of them was evaluated considering criteria such as costs, removal efficiency and flexibility. Once these aspects were analyzed by means of a prioritization matrix, using a panel of experts, the most effective treatment alternative was chosen to subsequently simulate at the laboratory level each of the unit operations of the selected alternative and thus define the conditions of operation and the experimental removal percentages.